2022
DOI: 10.1371/journal.pone.0265695
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian views regarding sharing of medical data for research: A cross-sectional study during COVID-19 pandemic

Abstract: Purpose In the current study, the views of Jordanian regarding sharing medical reports for research purposes were investigated during the COVID-19 pandemic. In addition, motivators and barriers regarding sharing of medical records were examined. Methods This observational survey-based cross-sectional study was conducted using an electronic questionnaire during the COVID-19 pandemic (second half of 2020). The questionnaire link was disseminated through two social media platforms (WhatsApp and Facebook), targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Health data, unlike other types of data, is highly personal and confidential and might affect individuals’ health, well-being, and personal lives. Its sensitivity extends to the risk of shame, stigma, or discrimination, a concern particularly prevalent in developing countries [ 25 , 26 ]. As AI systems typically involve collecting, storing, and analyzing sensitive patient information, these concerns are valid [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health data, unlike other types of data, is highly personal and confidential and might affect individuals’ health, well-being, and personal lives. Its sensitivity extends to the risk of shame, stigma, or discrimination, a concern particularly prevalent in developing countries [ 25 , 26 ]. As AI systems typically involve collecting, storing, and analyzing sensitive patient information, these concerns are valid [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that patients were more comfortable with the sharing of health information with health-related (non-commercial) organisations during the pandemic than prior to the pandemic, [1] although there are conflicting reports around levels of comfort with the sharing of health information for purposes related to COVID-19. [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%